An investigation on the awareness towards the issues that influence the usage of interlibrary loan among the bachelor of science in information studies (hons) (library & information management) (IM 220) students in UiTM Kedah / Mastura Mustapha - Mustapha, Mastura (Faculty of Information Management, 2012)
Interlibrary loan is a type of Reference Service in the library or Information Centre. It can hardly define as when a book or other item needed unavailable for some reason, or not owned by the library, a patron may request that it be borrowed from another library by filling out a printed interlibrary loan request form at a service desk, or electronically via the library's Web site. Some libraries also accept ILL requests via e-mail or by telephone, usually under exceptional circumstances. Materials borrowed on Interlibrary Loan usually renewed on or before the due date. The study is an investigation on the awareness towards the issues that influence the usage of Interlibrary Loan (ILL). The respondents of the study are among IM220 students who are consists of 243 students but the sample is about 150 students but only 148 was given back to the researcher. The factors that influence the study are time, awareness and cost. This study used Random Sampling in order to collect data from respondents. The Statistical Package for Social Science (SPSS) is used to analyse data.